SELF-DESCRIPTION AND OBSERVERS’ PERSPECTIVE TOWARD SCIENCE TEACHERS’ ABILITY IN USING QUESTIONING TECHNIQUE IN MIDDLE SCHOOL - Mazlina, Hilda; Halim, Abdul; Yusrizal, Yusrizal (Universitas Negeri Surabaya, 2018)
The study aimed at inquiring how science teachers use question technique in the teaching-learning process. The methodology used in this study was a survey method of quantitative approach. The population is all senior high school Physics teachers in Banda Aceh. The sample is the Physics teachers regarding their length of duty which were 6 teachers from 6 schools. The sampling technique was using disproportionate stratified random sampling based on the schools? accreditation. The data collection process was carried out by distributing the questionnaire to teachers and documentation technique by videotaping the learning process. The data were analyzed using a descriptive technique. The results showed that teachers used redirecting technique (70%) and probing technique (45.83%). Next, the teachers? experience only impacts the probing technique. A suggestion that can be made in teaching Physics, teachers should ask questions that track and test students? understanding toward a concept that they have learned.